2010
DOI: 10.1002/jor.21099
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic effects of interleukin‐1β on osteoblast differentiation in vitro

Abstract: A rat calvarial cell model of osteoblast differentiation using the formation of bone nodules in vitro as an endpoint was used to assess the effects of IL-1b on osteoblast differentiation. Short-term treatment (2 days) with IL-1b early in culture resulted in increased nodule number and size as well as calcium content in contrast to long-term treatment (6 days) in cultures assessed at 10-12 days. This increase in bone formation was blocked by IL-1 receptor antagonists. Short-term treatment increased COX-2, prost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“… found that the treatment of IL‐1β inhibited osteoblast maturation by up‐regulating the expression of cyclooxygenase‐2 and metalloproteinase to degrade the extracellular matrix of bone tissue. In contrast, short‐term exposure of IL‐1β promoted nodule formation , and the injection of IL‐1β accelerated endochondral ossification in mice bone fracture . Our data suggested that the exposure of IL‐1β did not inhibit osteogenic differentiation in hMSCs, consistent with a recent report published by Sonomoto et al.…”
Section: Discussionsupporting
confidence: 91%
“… found that the treatment of IL‐1β inhibited osteoblast maturation by up‐regulating the expression of cyclooxygenase‐2 and metalloproteinase to degrade the extracellular matrix of bone tissue. In contrast, short‐term exposure of IL‐1β promoted nodule formation , and the injection of IL‐1β accelerated endochondral ossification in mice bone fracture . Our data suggested that the exposure of IL‐1β did not inhibit osteogenic differentiation in hMSCs, consistent with a recent report published by Sonomoto et al.…”
Section: Discussionsupporting
confidence: 91%
“…As for the inflammatory stimulus, TNF-α and IL-β have been reported to inhibit cell osteogenic differentiation and subsequent bone formation (Schett 2011;Zhao et al 2012). However, several other reports support the finding that TNF-α promotes the osteogenic differentiation of human MSCs (Hess et al 2009;Glass et al 2011) and there is evidence that IL-1β elicits biphasic effects on in vitro cell osteogenic differentiation (Lin et al 2010). Alone or in combination, variations in the inflammatory condition design (e.g., cytokine dose and combination), cell incubation duration and differences in cell sources and donors (e.g., age and gender) may contribute to such disparities.…”
Section: Discussionmentioning
confidence: 89%
“…While, Hess et al (2009) reported that TNFalpha promotes osteogenic differentiation of human mesenchymal stem cells and Glass et al (2011) demonstrated that TNF-alpha promotes fracture repair by augmenting the recruitment and differentiation of muscle-derived stromal cells. Lin et al (2010) also showed that the biphasic effects of interleukin-1beta on osteoblast differentiation in vitro. Recently, Li et al (2014) revealed that lipopolysaccharide deteriorated the osteogenic differentiation of periodontal ligament stem cells through Toll-like receptor 4 mediated nuclear factor kappaB pathway, but not for bone marrow mesenchymal stem cells.…”
Section: Discussionmentioning
confidence: 93%